Soft Power and Vaccine Diplomacy: An Analysis of China's Global Image Enhancement during the COVID-19 Pandemic - Bilal Zubair; Sibra Waseem; Khushbakht Shahid (BTTN Journal, 2023)
The COVID-19 pandemic amplified global rivalries. The US blamed China for the viral outbreak in Wuhan. Many in the US, including former President Trump and his aides, called the Coronavirus the “Chinese Virus” or the “Wuhan virus,” raising anti-Chinese sentiments in the West. At the same time, Beijing sought to use this opportunity to practice its vaccine diplomacy to shore up its international stature as a world power amid the pandemic. In this pursuit, China provided vaccines and personal protective equipment (PPEs) as global public goods, particularly to the global South. Using both primary and secondary sources and relying on a mixed approach for data analysis, this paper analyzes the effectiveness of China’s vaccine diplomacy during Covid-19.  It explores China’s use of soft power through social media, including infodemics and ‘twiplomacy’ to bolster its image. The article also assesses the role of China’s ‘wolf warrior diplomacy’ that manipulated the facts to advance its propaganda. Conclusively, this paper argues that Chinese vaccine diplomacy served as an effective tool to enhance China’s global image as a responsible great power, albeit undermined through tactics such as the manipulation of information.